Tide and wind control of megalopal supply to estuarine crab populations on the Portuguese west coast - Queiroga, Henrique (2006)
Physical processes that force transport of planktonic larvae of invertebrates are responsible for some of the spatial and temporal variability in recruitment. We investigated the influence of tide- and wind-driven circulation on intra-year variability of megalopal supply to populations of the crab Carcinus maenas in 2 estuaries on the Portuguese west coast. Daily data on physical variables and on supply and settlement of megalopae were subjected to time series analysis and multiple regression techniques in order to identify periodicity in the variables as well as time lags between larval supply and physical variables. Relaxation of northerly winds, which favor upwelling, was associated with temperature increase and subtidal sea level rise at the coast, which are indicative of coastal convergence of the surface layer. Supply of megalopae to the estuaries, as measured with passive plankton nets, followed a fortnightly cycle with maximum larval supply at the time of maximum tidal amplitude. Supply was enhanced by southerly winds, with delays of 0 to –2 d. Settlement of megalopae on artificial settlement substrates deployed on the bottom was uncoupled to supply at both estuaries. Therefore, transport of C. maenas megalopae to the nearshore is accomplished by onshore advection following downwelling winds, and supply to the estuaries occurs by selective tidal stream transport. Involvement of internal waves and internal tidal bores cannot be be ruled out, but very particular periodicities of the generating mechanisms would have to be assumed to account for the observed time lags.